Artificial Stupidity: Data We Need to Make Machines Our Equals - Trazzi, Michaël (Patterns (N Y), 2020)
AI must understand human limitations to provide good service and safe interactions. Standardized data on human limits would be valuable in many domains but is not available. The data science community has to work on collecting and aggregating such data in a common and widely available format, so that any AI researcher can easily look up the applicable limit measurements for their latest project.